Tree Quality Volume Tables for Eucalyptus Hybrid - Chaturvedi, A. N. (Indian Forester, 1974)
Local volume tables are applicable to very restricted areas. Site quality volume tables are difficult to use in the field. Tree quality volume tables are easy to prepare and use in the field. Tree quality curves can be made independent of species. End use volume tables are suggested. Volume tables for Eucalyptus hybrid by four tree qualities are given.